Rancang Bangun Pembangkit Listrik Alternatif Menggunakan Termoelektrik dengan Memanfaatkan pada Tungku Pemanas - Muhammad Abdul Manap; Al Fikri (Journal of Electrical Power Control and Automation (JEPCA), 2020)
his study aims to design an alternative power generator using a thermoelectric generator (TEG) by utilizing a heating furnace, using two thermoelectric generators (TEG) connected in series. Thermoelectrics that take advantage of temperature differences can produce voltages that correspond to the seebeck effect. The alternative power generator that has been designed consist of a thermoelectric, boost converter, and a 5 Watt DC lamp load. The test was carried out using a Boost Converter and using a 5 Watt DC lamp load for 20 minutes. The results of the research using the Boost Converter produce a voltage of 42.8 V with a temperature difference of 90°C, while using a 5 Watt DC lamp load produces a voltage of 8.81 V with a temperature difference of 82°C and the resulting current is 0.6 A, the resulting power 4.84W.